Refusal of admission to a public primary school on the grounds of religion – an outline of liability from the perspective of private law (Discourse of Law and Administration, 2024)
The article presents the grounds for refusal to admit a pupil to a public primary school. At the outset, it was shown that the law does not indicate positive and negative criteria to be followed by the headmaster when making a decision on admitting a pupil to a school. On the other hand, the main part of the article focuses on describing the consequences of refusal to admit a student to a school due to his or her religion. Liability is described from the perspective of the provisions on general tort liability, as well as liability concerning the State Treasury and local government units, or other legal persons, as well as from the perspective of personal rights. Liability under other laws was also analysed.
Keywords: personal rights; belief; education; responsibility; school; responsibility of public authorities; discrimination; Islam